Method of estimation of characteristics losses of aircraft airworthiness - Ищенко, С. А.; Давидов, А. Р. (Proceedings of National Aviation University (archive), 2000)
Proposed is a new method of separation of degradation degree of characteristics of engine a&: airplane of a transport aircraft according to the results of interpretation of flight informatics registrated by regular airborne storage during regular flight. Demonstrated is actuality of the proposed method for maintaining airworthiness in accordance with ICAO recommendations. Given are the results of calculations of airplane and engine degradation degree received by means of aircraft Ил-86 flight mathematical model